20 Small group research in the east of england: a novel approach to palliative medicine research training. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Chin, Chloe; Grove, Sarah; Treaddell, Sarah; Barclay, Stephen; Spathis, Anna
Abstract : Background: Research is essential to advance the evidence base of Palliative Medicine. Few clinical trainees have the opportunity to become involved in research studies or to receive research training, which hampers trainees' ability to attain research competencies. Attending research courses may improve knowledge about research but are no substitute for participating in a study. Rotation of trainees also hinders completion of projects once started. Aim: To improve clinical trainee involvement in research to facilitate achievement of research competencies. Development of novel approach: A UK-wide survey of research training was undertaken. It found that over 75% of regions had no regular research training available. Only one region had a research training programme available for all Palliative Medicine trainees. A programme was devised whereby East of England trainees were organised pragmatically by job location into a small research groups. Four out of twelve monthly study days were dedicated to research projects and training. Two clinical academic Palliative Medicine consultants provided supervision and met with all project groups twice yearly for advice and guidance. Outcomes: Since programme inception in 2015, outputs have included two poster and one oral presentations at national and international conferences, and one peer-reviewed journal publication. Three further projects are ongoing. Prior to the programme, research outputs were rare. Participants report that project completion was facilitated by sharing workload amongst trainees, and by keeping projects location-based with newly rotating trainees providing continuity. The regional research meetings provided peer-to-peer support, the groups learning from each other's experiences. Conclusion: This novel approach has enhanced trainee research skills, experience and outputs. This form of research training programme could be readily adopted across the UK, being largely trainee-led: only intermittent support from consultants with an interest in research is needed.